2002
DOI: 10.1038/nature01136
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects of nitrogen additions on the stability and turnover of soil carbon

Abstract: Soils contain the largest near-surface reservoir of terrestrial carbon and so knowledge of the factors controlling soil carbon storage and turnover is essential for understanding the changing global carbon cycle. The influence of climate on decomposition of soil carbon has been well documented, but there remains considerable uncertainty in the potential response of soil carbon dynamics to the rapid global increase in reactive nitrogen (coming largely from agricultural fertilizers and fossil fuel combustion). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
436
4
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 696 publications
(497 citation statements)
references
References 21 publications
44
436
4
13
Order By: Relevance
“…However, several recent studies have shown, that a selective preservation of lignin appears to be only relevant during the early stages of litter decomposition and that later-on lignin degradation occurs at the same or even higher rate as the overall litter decomposition (Gleixner et al, 1999;Kerem et al, 1999;Jensen et al, 2005;Prescott, 2005;Kalbitz et al, 2006;Sollins et al, 2006). Recent studies using 13 C-CPMAS-NMR and pyrolysis techniques have confirmed that lignin is altered relatively quickly and does not appear to be stabilized in the long-term in any soil fraction (Baldock and Nelson, 2000;Gleixner et al, 2002;Kiem and Kögel-Knabner, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…However, several recent studies have shown, that a selective preservation of lignin appears to be only relevant during the early stages of litter decomposition and that later-on lignin degradation occurs at the same or even higher rate as the overall litter decomposition (Gleixner et al, 1999;Kerem et al, 1999;Jensen et al, 2005;Prescott, 2005;Kalbitz et al, 2006;Sollins et al, 2006). Recent studies using 13 C-CPMAS-NMR and pyrolysis techniques have confirmed that lignin is altered relatively quickly and does not appear to be stabilized in the long-term in any soil fraction (Baldock and Nelson, 2000;Gleixner et al, 2002;Kiem and Kögel-Knabner, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Our previous field investigations have shown that fungal biomass and fungi to bacteria ratios (Wang et al, 2015) and decomposition of lower-order roots and needles (Kou et al, 2015a(Kou et al, , 2015b) exhibited a decreasing trend at high NH 4 þ additions. Moreover, long-term elevated N input has been found to enhance chemical stabilization of organic matter into recalcitrant compounds that are resistant to microbial decay (Neff et al, 2002;Swanston et al, 2004), thereby potentially impairing fungal metabolism (Maaroufi et al, 2015). With increasing additions of NH 4 þ , microbial NH 4 þ cycling shifted from a state of decoupling (gross NH 4 þ immobilization rates were incomparable to gross N mineralization rates) to coupling (gross NH 4 þ immobilization rates were comparable to gross N mineralization rates).…”
Section: The Effects Of Nhmentioning
confidence: 99%
“…Porém, a fertilização, principalmente com adição de N, pode auxiliar diretamente na estabilização de formas orgânicas do C no solo, aumentando, também, os estoques de C e N em frações mais humificadas da MOS, conforme verificado no sistema fertirrigado. NEFF et al (2002) demonstraram que a fertilização com N acelerou a decomposição das frações leves da matéria orgânica com tempos de ciclagem em torno de décadas, mas auxiliou na estabilização das frações de C das substâncias húmicas associados à fração mineral e que possuem tempo de ciclagem de décadas (STEVENSON, 1994). Tal hipótese é corroborada pelo incremento nos estoques de N nas substâncias húmicas, em especial nos ácidos húmicos e huminas (Figura 2).…”
Section: Resultsunclassified
“…recalcitrantes, abundantes em resíduos vegetais de eucalipto, favorecendo seu acúmulo nas substâncias húmicas, pela sua menor suscetibilidade à ação de enzimas lignolíticas (NEFF et al, 2002).…”
Section: Resultsunclassified
See 1 more Smart Citation